Optical Control of Bulk Phonon Modes in Crystalline Solids. Issue 2 (17th December 2021) - Gao, Yuan‐Fei; Lai, Jia‐Min; Zhang, Jun
Abstract: Long‐lived phonons within crystalline bulk acoustic wave (BAW) resonators have become coherent carriers of information, which can be utilized for a variety of scientific and technological applications. Herein, a brief introduction to the field of phonon control is given with an emphasis on bulk phonons at high frequencies within crystalline solids. In cavity optomechanics, the photons and phonons can be confined by material boundaries, yielding large optomechanical coupling rates at gigahertz (GHz) frequencies, but the spurious heating is detrimental to robust operation. Although electromechanical techniques can be used to access long‐lived phonons in piezoelectric crystals, they are not suitable for the study of non‐piezoelectric crystals. The phase‐matched Brillouin interactions enable efficient optical access GHz frequency mechanical modes within macroscopic crystalline solids. Combining with the well‐established framework of cavity optomechanics, efficient optical control of BAWs can be obtained. For optical phonons, strong spontaneous Raman cooling and heating based on the interaction between excitons and phonons are considered. In addition, the application of optical phonons in quantum memory at room temperature is introduced. The review finishes with a discussion of the research direction for bulk optomechanical systems and exciton–phonon coupling systems in the future. Abstract : Efficient control of phonons has sparked broad interests in phononic device physics and technologies. This paper reviews recent advances in optical control of the bulk phonons within crystalline solids. Compared to traditional cavity optomechanics, the new optomechanical systems utilizing bulk phonons instead of macroscopic mechanical mode are promising platforms for experiments in the quantum regime.